USO DE PRÓTESIS BIOLÓGICA PARA EL TRATAMIENTO DE FÍSTULAS PERIANALES COMPLEJAS (Revista Argentina de Cirugía, 2022)
Background: The treatment of complex anal fistulas is controversial. Using low-invasive treatments as an alternative to conventional surgery reduces the risk of complications and sequels.Objective: To evaluate the feasibility of the procedure and the initial results of using porcine biological prosthe- ses (PBP) for treating complex anal fistulas.Materials and Method: An observational prospective study on the use of PBP in patients with complex anal fistulas was carried out between September 2006 and April 2007. Patients with inflammatory bowel disease, simple fistulas or acute suppurative processes were excluded. Before surgical intervention, all patients were subjected to a proctological examination, endorectal ultrasound and manometry. Early postoperative follow-up was performed 7 and 15 days after surgery, and from then on patients were evaluated every 30 days. The Jorge and Wexner incontinence scale was used to assess fecal continence.Results: A total of 13 patients were evaluated, seven men and six women. The average age was 57 ± 16 years. The repaired fistulas were transsphincteric in 12 cases (92 %) and 1 patient had horseshoe fistula. The mean length of the fistulous tract was 5.1 ± 1.2 cm. The incontinence score previous surgery was 7 ± 1.2, and postsurgical incontinence was zero. One patient presented more than one fistulous tract. Three patients (23%) were treated with setons 19 weeks before the PBP surgery. No complications were registered during surgery and the morbility rate was of 23%. The prosthesis was spontaneously expelled in three patients.
Keywords: perineal fistula; biological prosthesis